Assessment of biological literacy for high school students - Suhadi, Anggi Putri; Ristanto, Rizhal Hendi; Sigit, Diana Vivanti; Supriyatin, S (Biosfer: Jurnal Pendidikan Biologi, 2023)
Biological literacy is the individual's ability to determine the prior knowledge to understand the terms, concepts, procedural, benefits, and relationships of biological sciences in life. This study aims to measure students' biological literacy skills. This study approach was conducted descriptively, with grades, levels, and material indicators utilized to assess biological literacy skills. The population in this study was students from grade X Mathematics and Natural Sciences, Baitul Qurro Islamic Senior High School, with a sample size of 44 students drawn from the overall population. The instrument employed was a multiple-choice with up to 15 items about viruses related concepts. The data were analyzed descriptively. The results of this study revealed that 50% of students have low biology literacy skills. The highest percentage of students' biological literacy skills was found in indicator 4 (interpreting the role of viruses in life), 61%, while the lowest was in indicator 3 (analyzing virus replication), with 42%. The percentage of students' literacy skills in each level of biological literacy was highest at the structural level, with 58%, while the lowest was at the nominal level, with 44%. The low level of student biological literacy indicates that research is needed to find the right strategy to improve biological literacy skills in learning.